COVID-19 in Russia. Spring-Summer Period of the Pandemic 2020 - L. S. Karpova; D. A. Lioznov; K. A. Stolyarov; N. M. Popovtseva; T. P. Stolyarova (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. The actuality of the study is due to the beginning of a new rise in the incidence of COVID-19 in the autumn of 2020 in the world and the need to study the features of the COVID-19 epidemic process for monitoring and forecasting the epidemic situation for its spread. Aim. Identification of features of morbidity, from March to September 2020 was based on data from the Ministry of health of Russia on the incidence and mortality from COVID-19 and from the date Influenza Research Institute on the weekly incidence of COVID-19, hospitalization and deaths in various age groups in 48 cities located in 8 Federal districts. Results. The dynamics of weekly morbidity and mortality in the Russian population from COVID-19 is presented. A noticeable increase in the incidence began from March 30 to April 5, 2020, and the peak of the epidemic was registered 6 weeks later. Within 3 months, the incidence decreased by more than 2 times and was minimal at the end of August. The order of involvement of Federal districts in the COVID-19 epidemic has been determined. The indicators of morbidity, hospitalization, and mortality were calculated, and the role of various age groups in the morbidity and mortality of the population from COVID-19 was shown. Differences in morbidity and mortality in Federal districts are shown. Conclusion. The rise in morbidity in Russia began much later than in Europe, in the week of the peak of the epidemic in this region. The epidemic started in the Southern FD, then in the Central and Far Eastern FD, and then every week-in the Siberian, Volga and Ural FD, and 3 weeks later (in June)-in the North-Western and North-Caucasian FD. By the beginning of the seasonal rise in ARI, morbidity and mortality rates remained high, especially in the Far Eastern and North-Western districts. The incidence of the adult population was 2.5-3.4 times higher than that of children. The mortality rate among people over 65 years of age was 8.8 times higher than among those aged 15-64 years. In the total population incidence of COVID-19, the proportion of people aged 15-64 years was 74.3%, and in mortality from COVID-19 - 34.1%, and those over 65 years, on the contrary, in morbidity -18.6%, and in mortality -65.9%. The highest rates of morbidity and mortality were found in the Far Eastern, Southern, Siberian and Central districts with a high incidence, primarily of people over 65 years of age. Lethality rates were higher in districts with a low rate of hospitalization.